The impact of TP53 co-mutations and immunologic microenvironment on outcome of lung cancer with EGFR exon 20 insertions. (July 2022) - Christopoulos, Petros; Kluck, Klaus; Kirchner, Martina; Lüders, Heike; Roeper, Julia; Falkenstern-Ge, Roger-Fei; Szewczyk, Marlen; Sticht, Florian; Saalfeld, Felix C.; Wesseler, Claas; Hackanson, Björn; Dintner, Sebastian; et al.
Abstract: Background: EGFR exon20 insertions (ex20ins) are targeted by novel compounds in non-small-cell lung cancer (NSCLC). However, data about outcome under conventional therapies and the influence of molecular features are scarce. Patients and methods: We retrospectively analysed 118 patients with evaluation of radiologic response based on RECIST v1.1. TP53 status was available for 88 cases. Results: Platinum doublets and chemoimmunotherapy showed similar response rates (20–25%), disease control rates (80%) and median progression-free survival (mPFS, ≈7 months), which were longer compared to monochemotherapy (9%, 59%, 4.1 months), EGFR inhibitors (0%, 46%, 3.0) and PD-(L)1 inhibitors (0%, 30%, 2.1; p < 0.05). Overall survival (OS) was not dependent on the choice of first-line treatment, but related to more lines of systemic therapy (p < 0.05). TP53 mutations and brain metastases were associated with shorter PFS under platinum doublets and EGFR inhibitors (HR 3.3–6.1, p < 0.01), and shorter OS for patients receiving both treatments (p < 0.05). More tumour CD8 + and less Th1 cells were associated with longer OS independent of brain and TP53 status (p < 0.01). No difference in outcome was noted according to the ex20ins site and use of pemetrexed ( vs. other cytotoxics) or bevacizumab. Long-lasting responses (>1 year) occasionally occurred under EGFR inhibitors for both 'near-' and 'far-loop' variants. Conclusions: Platinum doublets and chemoimmunotherapy have the highest activity with ORR of 20–25% and mPFS of approximately 7 months, regardless of the cytotoxic partner, while PD-(L)1 inhibitors show limited efficacy. TP53 mutations, brain metastases and a lower tumour CD8/Th1-cell ratio are independently associated with shorter survival. Highlights: Platinum doublets and chemoimmunotherapy showed similar efficacy with ORR 20–25%. TP53 mutations and brain metastases conferred shorter survival after platinum and TKI. More tumour CD8+ and less Th1 cells were associated with longer overall survival. No difference in outcome by exon20 insertion site or use of pemetrexed or bevacizumab. Occasionally long responses under EGFR TKI for both 'near-' and 'far-loop' variants.